Discovering the Essence of Spiritual Resilience of Patients Receiving Continuous Ambulatory Peritoneal Dialysis: A Study of Hermeneutic Phenomenology - Thong-on, Rattiya; Kaewkerd, Onuma; Chaiyasit, Yuttachai; Waiwitriyaku, Niphathorn (The Bangkok Medical Journal, 2025)
OBJECTIVES: This study aimed to explore the essence of spiritual resilience in patients receiving continuous ambulatory peritoneal dialysis (CAPD). MATERIALS AND METHODS: The research design employed Van Manen’s hermeneutic phenomenology. Purposive sampling was utilized to select thirty participants. Semi-structured in-depth interviews were conducted from August 2023 to January 2024 to collect data. RESULTS: The study found that patients defined spiritual resilience through reflections on Van Manen’s five lived worlds: 1) Lived space: Home gives me life; 2) Lived body: Letting go; 3) Lived time: Time to leave love behind; 4) Lived relationships: The people around you are important; and 5) Lived things: Dialysis gives life, not just time. CONCLUSION: Spiritual resilience among CAPD patients is deeply rooted in their lived experiences, reflecting a holistic integration of physical, emotional, and spiritual adaptation to chronic illness. Healthcare providers should incorporate spiritual and existential support into CAPD care to enhance patients’ well-being and resilience, with interventions tailored to the personal and cultural meanings patients assign to their illness and treatment, aiming to support treatment adherence, bolster dialysis success, and protect against depression.